PENGEMBANGAN MEDIA PEMBELAJARAN FISIKA BERBASIS ANIMASI FLASH MATERI USAHA DAN ENERGI UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA - Raidaturrahmah, Raidaturrahmah; Sukroyanti, Baiq Azmi; Gummah, Syifa’ul (Jurnal Ilmiah IKIP Mataram, 2018)
This study aims to develop the Theaching Media based Flash Animation Materials Business and Energy to improve students’ conceptual understanding. Testing the feasibility of teaching media through the 2 validator, namely Master of Material and Design of Media. This studyÂ use ADDIE development model that is Analysis, Design, Development, Implementation and Evaluation. Validation results by two expert lecturers to the flash animation based teaching average of 3.3 with the category is very valid. Further validation was done to 23 students of class VIIIA SMPN 16 Mataram based on the contents of the material and All component of teaching media of all students with an average of 3.4 classified strongly agree. Then on the conceptual understanding test of student obtained an average of 3.7 is very good. Thus development of physics teaching media based flash animation business and energy material to increase conceptual understanding of student feasible applied in schools.